Evaluation of the efficacy and surgical-related safety of neoadjuvant immunochemotherapy in advanced resectable none small cell lung cancer (NSCLC) - Wang, Qin; Qi, Chen; Luo, Jing; Xu, Nan; Xu, Mao-tian; Qiang, Yong; Zhang, Chi; Shen, Yi (Frontiers in Oncology, 2023)
Background: The emergence of immune checkpoint inhibitors (ICIs) has brought about a paradigm shift in the treatment landscape of non-small cell lung cancer (NSCLC). Despite the promising long-term survival outcomes and optimization of pathological complete response (cPR) demonstrated by various studies such as Impower010 and Checkmate-816, the effectiveness of neoadjuvant immunotherapy in advanced resectable NSCLC remains a subject of debate. Although previous research has explored the connection between the efficacy of neoadjuvant therapy and surgicalrelated safety, limited studies have specifically investigated the surgical-related safety of neoadjuvant immunotherapy. Therefore, our study aims to assess the efficacy and surgical-related safety of neoadjuvant immunotherapy in advanced resectable nonsmall cell lung cancer. Method: We conducted a retrospective study on a cohort of 93 patients with stage IIIA-IIIC NSCLC who underwent neoadjuvant therapy and surgical resection. Among them, 53 patients received neoadjuvant immunotherapy, 18 patients underwent neoadjuvant chemotherapy while the remaining 22 underwent neoadjuvant targeted therapy. The patients were separated into further groups according to their pathological type. Data analyses were performed using Mann-Whitney U test, chi-square test. Results: All patients were categorized into six distinct groups.